Models of financing football clubs in the biggest European leagues - Talovic, M.; Ormanovic, S.; Kljaho, A.; Ciri, A.; Jeleskovic, E.; Alic, H.; Dedovic, D. (Sportski Logos, 2017)
Football world is always related to numbers. Bigger numbers contribute to the bigger financial solvency and attract players, players attract fans to the stadiums, and sponsors. There is a bad trend in football business world where costs are bigger than the revenue. The countries in which clubs are successful for years are the exceptions . (Germany, Portugal, Austria, England). Models of business in Germany, with popular "50+1" model of management structure in clubs contributed to the development of the sport, football and stabilization of Bundesleague and better public relations with transparent activities. The rule "50+1"is a term which is used as regulation in German football league. Clause, the rule, which statesthat majority of voting structure in clubs, must keep the club and members of the club, respectively. This enables members of the club to have the majority and to protect the club from the outside investors. English football is based on the opposite model. English model of management structures is set so that majority of the clubs is in private ownership, and, therefore dependable on money of an individual, TV rights, and great loans with favourable interest rates. Other leagues (Portugal) base their revenue mainly on transfers of young players. French league, with the exception of PSG and Monaco, also base their revenue on transfers of young players and sponsorships. Italian league is not an attractive market for investors, for a long time now, which creates problems for financing the clubs, which spend up to 75% of their incomes on salaries of the employees and the players. German model "50+1" lead to the development of football in Germany, better relations with the local companies related to sport, and keeping the club in hands of the fans and members of the club, respectively. Synergy of the local community, fans and the big companies creates money.